The Purchasing Power of Money and Nominal Interest Rates: A Re-Examination - Shome, Dilip K.; Smith, Stephen D.; Pinkerton, John M. (Journal of Finance, 1988)
While it has been known for some time that, under uncertainty, the original version of the Fisher hypothesis is not precisely correct, empirical researchers have largely ignored this fact. Such an omission has possibly resulted in erroneous conclusions concerning other hypotheses; most notably the impact of prices on the real economy. This paper clarifies some of the previous interpretations of the existing empirical literature and provides a theoretical version of the relation between prices and interest rates. Empirical tests based on both the Livingston survey data and data from time-series forecasting models provide support for the Fisher effect and the hypothesis that only covariance risk is priced in the Treasury bill market.